A rare case of eye complications of gastric stromal tumor treatment using imatinib mesylate - E. B. Myakoshina; S. V. Saakyan (Российский офтальмологический журнал, 2020)
Purpose: to describe a clinical case of ocular complications of gastric stromal tumor treatment with imatinib mesylate.Material  and methods. A patient aged 78 was examined  by general ophthalmologic and instrumental  methods,  including ultrasound  and spectral optical coherence tomography (SOCT).Results. Ophthalmoscopy  helped diagnose a blunted foveal reflex of the right eye. In the left eye, fuzzy boundaries of the optic disc edema and the macular reflex, the presence of gray-yellow foci of an irregular shape with even distinct boundaries in the paramacular zone were revealed. In the lower part of the left eye fundus, a weakly pigmented gray-yellow focus with uneven indistinct boundaries and an uneven  surface was to be seen. SOCT showed in the right eye a retinal edema in the macula  and paramacular  zones and an epiretinal membrane.  In the left eye, SOCT showed vitreoretinal tractions and retinal edema on the edges of the optic nerve; in the paramacular  zone and in the inner parts of the fundus,  vitreoretinal tractions, epiretinal fibrosis, retinal edema was observed whilst in the lower parts of the fundus complete destruction of all retinal layers due to the hyperreflective focus with a small-shaped inner contour, an even choroidal profile with thinning of the choroid, vitreoretinal tractions, and epiretinal membrane  in the left eye could be seen.Conclusions. The clinical case of eye complications of imatinib mesylate in the treatment of gastric stromal tumor necessitates an interdisciplinary integrated approach (involving an oncologist and an ocular oncologist) in the diagnosis and treatment of eye tumors. A complex of instrumental methods of diagnostics of eye fundus diseases involving additional refinement methods (SOCT) ensures differential diagnosis of retinopathy during the chemotherapy, secondary metastatic involvement, and vitreoretinal pathology of a different pathogenetic etiology. Early diagnosis facilitates providing adequate treatment aimed at preserving the patient’s vision, the eye, and life.